Clinical profile and outcome of snake bite in children - Meshram, Rajkumar M.; Bokade, C. M.; Merchant, Saira; Bhongade, Swapnil (International Journal of Contemporary Pediatrics, 2017)
Background: Snake bite is generally considered to be a rural problem and has been linked with environmental and occupational condition is a neglected public health problem. This study was conducted to ascertain clinical profile, complication and outcome of snake bite in pediatric population. Methods:Retrospective observational study was done in paediatrics wards and Paediatric Intensive care unit of tertiary care institute. A medical record files of 80 patients of snakebite, between the periods of January 2011 to February 2016 were recovered from Medical Record and Statistics Section of Institute. Files were analyzed for demographic data; variables included site of bite, time of bite, type of primary treatment and treatment provider, and type of snake poison, common symptoms suggestive of hematotoxicity, myotoxicity and neurotoxicity. Results: Out of total 80 patients, 58.75% were male and most of snake bites were seen in age group of 6-12 years. Clinically 57.5% patients were presented with signs and symptoms of envenomation and most of them were bitten during the months of June to September. All bites were nonprovocative and in 57.5% lower limb was the commonest site of bite. A 77.5% patient were primarily treated by medical personnel, 56.25% patients were received treatment within 1 hour of bite and hospitalized within 6 hours of bite. Coagulation failure was commonest complication (58.33%) followed by hypotension (25%) in vasculotoxic snake bite and respiratory paralysis (68.18%) in neuroparalytic bites. Renal replacement therapy was required in 5%, blood/blood product transfusion in 11% patients and case fatality rate was 11.25%. Conclusions: The most vulnerable to snake bites are boys aged more than 5 years. There is an urgent need to spread awareness among the community for avoidance of traditional treatment and any delay in medical intervention in snakebite incidents.